Relationship Between Teacher Creativity in Online Learning and PAI Learning Achievement at Private Vocational School 1 Berau - Samsiadi, Samsiadi; Khozin, Khozin; Humaidi, M. Nurul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aimed to test the theory that links student achievement in PAI learning, which is influenced by teacher creativity in online education at SMK Negeri 1 Berau. The method used in this study is a quantitative approach to the type of correlation research that is ex-post facto. The population and sample of this study were PAI teachers and class XI students at SMK Negeri 1 Berau. The sampling technique used is nonprobability sampling, namely systematic sampling. The results of testing the hypothesis show that teacher creativity in online learning with PAI learning achievements of students of SMK Negeri 1 Berau obtained a correlation coefficient of 0.792 with a significance level of 0.000. The correlation number obtained is marked positive, meaning it has a unidirectional relationship. While the significance level of 0.000 <0.05 means a strong relationship. Based on the hypothesis test results, the results show that Ha is accepted. H0 broke the meaning that there is a strong relationship between teacher creativity in online learning and student achievement in PAI at SMK Negeri 1 Berau. The contribution of teacher creativity is significant in improving student achievement. The higher a teacher's creativity level, the better student achievement.